Gynecological health care services utilization and violence among female sex workers in Togo in 2021 - Alexandra M. Bitty-Anderson; Akila W. Bakoubayi; Fifonsi A. Gbeasor-Komlanvi; Arnold J. Sadio; Patrick A. Coffie; Didier K. Ekouevi (Reproductive Health)
Abstract Background Female Sex Workers (FSW) in Sub Saharan Africa face multiple challenges increasing their vulnerability to poor health, particularly poor sexual and reproductive (SRH) health outcomes and violence. The aim of this study was to assess the use of gynecology health care services and factors associated with its use as well as experiences of violence among FSW in Togo. Method A cross-sectional study was carried out in 2021 among FSW in two cities of Togo. A snowball sampling method was used and initial seeds were identified in each site in collaboration with FSW non-governmental organizations. A logistic regression was performed to identify factors associated with the use of a SRH service and violence. Results A total of 447 FSW with a median age of 30 [IQR: (24–38)] participated in this study and 43.4% of them had reached at least secondary school. Among them, 29.1% reported having been to a gynecological consultation over the previous year. Factors associated with a gynecological consultation included: living in the Lomé capital city (aOR = 0.35, 95%CI 0.22–0.54), and an experience of condom breakage or slippage (aOR = 2.00; 95%CI 1.19–2.64). The majority reported at least one lifetime pregnancy (87.9%), 39.8% reported ever having an unintended pregnancy and 67.6% of them ever had an abortion. Finally, 61.1% indicated being victims of physical, sexual, or emotional violence in the previous six months. Sex workers living in Lomé (aOR = 1.78; 95%CI 1.16–2.73); a history of abortion (aOR = 1.53; 95%CI 1.03–2.31) and having more than 15 clients per week (aOR = 4.87; 95% CI 1.99–11.94), were more likely to experience violence. Conclusion There is an under-utilization of health care services among FSW in Togo in addition to overall poor sexual and reproductive health outcomes with a high prevalence of gender-based violence. Those results highlight the importance of continued advocacy for the integration of SRH care with HIV prevention services geared toward FSW as well as a holistic approach to SRH care with innovative ways to prevent violence.